Oikumenitas dan Solidaritas menurut Dokumen Teologi Gereja HKBP - Purba, Daniel Rizki; Sianipar, Efran Mangatas; Hasibuan, Ricky Pramono; Harianja, Mikael (Diligentia: Journal of Theology and Christian Education, 2024)
This article discusses the crucial role of the church in addressing global challenges such as environmental crises and social injustices. Through an examination of the Theological Document of the Huria Kristen Batak Protestant Church (HKBP), this article highlights the concepts of ecumenism and solidarity as the foundation for the church's actions in safeguarding the environment and supporting social welfare. Considering the negative impacts of modernization on the environment and society, HKBP emphasizes the importance of active involvement in environmental restoration and protection efforts, as well as combating all forms of discrimination. The article also depicts the role of HKBP as a catalyst for change, promoting inter-church cooperation in bringing liberation to all of God's creation. With a focus on the practical implementation of its theological doctrines, this article provides an insight into how the church can effectively become an agent of social justice advancement and environmental preservation.BAHASA INDONESIA ABSTRACTArtikel ini membahas peran penting gereja dalam menjawab tantangan global seperti krisis lingkungan dan ketidakadilan sosial. Melalui telaah terhadap Dokumen Teologi Gereja Huria Kristen Batak Protestan (HKBP), artikel ini menyoroti konsep Oikumenisme dan solidaritas sebagai landasan tindakan gereja dalam menjaga lingkungan dan mendukung kesejahteraan sosial. Mempertimbangkan dampak negatif modernisasi terhadap lingkungan dan masyarakat, HKBP menekankan pentingnya keterlibatan aktif dalam upaya restorasi dan perlindungan lingkungan, serta memerangi segala bentuk diskriminasi. Artikel ini juga menggambarkan peran HKBP sebagai katalisator perubahan, mendorong kerja sama antar-gereja dalam membawa pembebasan bagi seluruh ciptaan Tuhan. Dengan fokus pada implementasi praktis dari doktrin-doktrin teologisnya, artikel ini memberikan gambaran tentang bagaimana gereja dapat secara efektif menjadi agen kemajuan keadilan sosial dan pelestarian lingkungan.